2013
DOI: 10.1111/dsu.12200
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Light Therapy for Androgenetic Alopecia: A 24-Week, Randomized, Double-Blind, Sham Device–Controlled Multicenter Trial

Abstract: LLLT could be an effective treatment for AGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 17 publications
7
91
0
Order By: Relevance
“…[67] Moreover, combining LLLT with topical minoxidil solution and oral finasteride may act synergistic to enhance hair growth. Due to the known beneficial effect on wound healing, it is conceivable that LLLT as an adjunctive therapy in hair transplant surgery may also reduce postoperative shedding, reduce healing time, and increase graft patency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[67] Moreover, combining LLLT with topical minoxidil solution and oral finasteride may act synergistic to enhance hair growth. Due to the known beneficial effect on wound healing, it is conceivable that LLLT as an adjunctive therapy in hair transplant surgery may also reduce postoperative shedding, reduce healing time, and increase graft patency.…”
Section: Resultsmentioning
confidence: 99%
“…These effects in turn lead to increased cellular proliferation, modulation in levels of cytokines, growth factors and inflammatory mediators, and increased tissue oxygenation. While the effects of these biochemical and cellular changes have broadly been studied in both animal models and clinical studies with patients, and have shown benefits in diverse conditions, such as increased healing in chronic wounds, improvements in sports injuries and carpal tunnel syndrome, pain reduction in arthritis and neuropathies, and amelioration of damage after heart attacks, stroke, nerve injury and retinal toxicity,[79] the effects on hair growth stimulation have only recently gained the attention of the scientific community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finasteride with or without minoxidil is equally well-tolerated and increased hair density in a small cohort of adolescent boys (100). Recent studies have also demonstrated efficacy of low-level laser therapy for adult patients of both genders with AGA (104106). …”
Section: Other Patterned Alopeciamentioning
confidence: 99%
“…More studies, including RCT are needed to support its efficacy. In addition, the optimum dose, wavelength, coherence and dosimetric parameters remain to be determined [113,116,117,110].…”
Section: Low-level Laser Therapymentioning
confidence: 99%